De-growth: A Practical Path to Just Sustainability - Nuryananda, Praja Firdaus; Rudiany, Novita Putri; Hamdan, Arva Rizqullah; Zein, Isynariyah; Bilqis, Thufailah Nafiisah (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
There are challenges and contradictions presented by the green economy, and its derivative, namely green growth, including the phenomenon of greenwashing and the sustainability paradox. The green economy has the potential to cause technological determinism in sustainable development. This article attempts to reintroduce and amplify the idea of ​​de-growth, which was once a manifestation of post-pandemic recovery in 2020 as a form of economic re-orientation towards sustainable development. This article, written with a qualitative approach and literature study instruments, also portrays de-growth globally and in Indonesia, especially for the tourism sector with examples in Raja Ampat and Nusa Penida. We can examine the application of de-growth as an economic principle in Raja Ampat and Nusa Penida through restrictions on the number of tourists, zoning areas, and the involvement of existing local communities.